Positivity Rate of Pyrosequencing to Diagnose Drug-Resistant Tuberculosis Directly from Sputum with Different Bacterial Load - Selma Zein Syafira; Nabilla Ghina Zavitri; Su Yan; Yunia Sribudiani; Alexander Lezhava; Lidya Chaidir (The Indonesian Biomedical Journal, 2020)
BACKGROUND: Molecular techniques, which detect mutations associated with drug resistance tuberculosis (TB), are promising technologies for rapid diagnosis and monitoring of drug-resistant TB. Pyrosequencing is a potential rapid and robust molecular technique to detect drug resistance but its performance in clinical samples is less investigated. This study aimed to determine the positivity rate of pyrosequencing to diagnose drug-resistant TB directly from sputum samples with different grades of sputum smear microscopy results.METHODS: Thirty-five sputum specimens from drug-resistant TB suspects were submitted for acid-fast bacilli (AFB) microscopy. All specimens were cultured using microscopic observation drug susceptibility (MODS) culture. Pyrosequencing was performed to DNA extracted from sputum of culture-positive patients.RESULTS: MODS culture was positive in 19/35 subjects (54.29%) samples; 16 smear-positive and three smear-negative. Using pyrosequencing, Mycobacterium tuberculosis was identified in all culture-positive samples, including smear-negative samples. A complete resistance profile for 16 (82.35%) samples could be generated. Pyrosequencing failed to show results for eis or gyrA promoter in three samples. Nine of 19 patients were multidrug resistant-TB (MDR-TB), 1/19 was rifampicin-resistance TB (RR-TB), and 4/19 were pre-extensively drug-resistant TB (pre-XDR-TB). Two novel mutations in rpoB and rrs (associated with rifampicin and aminoglycoside, respectively) were found in this study.CONCLUSION: The results of this study demonstrates high positivity rates of pyrosequencing to detect drug-resistant TB directly from sputum samples with different grades of smear microscopy, as the surrogate of bacterial load. The assay can be used as a first prediction test of drug resistance prior to confirmation by phenotypic tests.KEYWORDS: drug-resistant tuberculosis, pyrosequencing, direct sputum